Security Aspects in Information Technology First International Conference, InfoSecHiComNet 2011, Haldia, India, October 19-22, 2011. Proceedings - Joye, Marc; Mukhopadhyay, Debdeep; Tunstall, Michael (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the First International Conference on Security Aspects in Information Technology, High-Performance Computing and Networking held in Haldia, India, in October 2011. The 14 full papers presented together with the abstracts of 2 invited lectures were carefully reviewed and selected from 112 sumbissions. The papers address all current aspects in cryptography, security aspects in high performance computing and in networks as well. The papers are divided in topical sections on embedded security; digital rights management; cryptographic protocols; cryptanalysis/side channel attacks; and cipher primitives.